TUNNEL COOLING FOR BYRD STATION, ANTARCTICA - 1968 PROGRESS REVIEW. - Hoffman,Clark R. (1969)
Byrd Station is an underground facility occupying snow tunnels in the continental ice shelf of Antarctica. An experimental supplementary snow-plenum air-cooling system is being installed in the principal heat-producing tunnel at this station towards maintaining the 0F design air temperature in this tunnel during summer. Military construction progress on the plenum during the summer of Deep Freeze 68 (DF-68) is presented along with instrumentation of the snow mass over the plenum by the Naval Civil Engineering Laboratory (NCEL). Transient temperature gradients based on winter temperatures in this snow mass are also presented for the winter of DF-68-69. NCEL observations on the Byrd tunnels during the summer of DF-68 are compared with other inspections at Byrd Station. These include air temperatures, ventilation and maintenance problems in both the heat-producing and nonheat-producing tunnels. (Author)